A multiple-case study of high school students' biology test-preparation : an exploration of what students do and why they do it - Buchanan, James Alan (School of Education, 2016)
The South African schooling system is criticised for having low pass rates and marks inflated by low standards, and is seen as partially accountable for the high drop-out rates among the 'academically successful' students who make it to university. Remediation attempts have been made through curriculum changes but achievement in the schooling system continues to rely heavily on marks in tests and examinations, yet test-preparation in South Africa is poorly researched. This study regarded test-preparation as an overlooked area of possible remediation and aimed to explore test-preparation practices by asking what students do as they prepare for tests, what the thinking is behind their actions, and what leads them to prepare as they do. Self-regulated learning (SRL)(Zimmerman, 1989) was selected as the appropriate conceptual lens, which saw this research guided by the field's principal dimensions, namely, behaviour, metacognition, and motivation. The research methodology was influenced by calls from the SRL field for naturalistic research of test-preparation that takes students views into account; hence an exploratory, multiple-case study approach was adopted. Cases comprised six male and five female, Grade 11 students from four private and state schools writing the state examination in the Western Cape of South Africa, a top-performing province in national educational rankings. Schools placing strong emphasis on providing access to university were chosen as a 'best-case' scenario of test-preparation. Students' 'typical' test-preparation for Biology was explored in light of a standardised target test. Diaries, supported by study artefacts, were used to collect data about students' preparation over the seven days before the test. This was supplemented by semi-structured, post-test interviews conducted with individual students, and their teachers and parents.